Immigration & Credentialing: A Case Study of Jamaican Teachers in 1960s Alberta - Jennifer Kelly; Dan Cui (Adult Education Research Conference, 2007)
This paper examines the experiences of Jamaican teachers who immigrated to Alberta during the early 1960s. Using teacher narratives as well as archival research the paper aims to develop an understanding of issues related to racialization, immigration and citizenship.